Impact of sex difference on survival of bladder cancer: A population‐based registry data in Japan. (27th March 2019) - Nakayama, Masashi; Ito, Yuri; Hatano, Koji; Nakai, Yasutomo; Kakimoto, Ken‐ichi; Miyashiro, Isao; Nishimura, Kazuo
Abstract : Objective: To investigate the impact of sex on the prognosis of bladder cancer in Japan. Methods: In total, 18 728 patients diagnosed as having bladder cancer from 1993 to 2006 were registered in population‐based cancer registries of six prefectures in Japan. We estimated relative survival by sex, age, clinical stage at initial diagnosis and pathology. Results: Patients included 14 203 men (75.8%) and 4525 women (24.2%). The stage at initial diagnosis in women was significantly higher than in men ( P  <   0.0001). Pathologically, women were more likely to have non‐urothelial cancer than men (women 18.0%, men 9.5%, P  <   0.0001). The 5‐year relative survival was 80.3% for men and 67.7% for women. The 5‐year relative survival was 93.0% for men and 87.7% for women in the localized cancer group, 34.8% for men and 23.9% for women in the locally advanced cancer group, and 7.1% for men and 8.3% for women in the metastatic cancer group. The relative survival of women was worse than that of men in the localized cancer group (hazard ratio 1.29, 95% confidence interval 1.05–1.57; P  =   0.0145) and locally advanced cancer group (hazard ratio 1.32, 95% confidence interval 1.15–1.52; P  =   0.0001), but not different in the metastatic cancer group (hazard ratio 1.04, 95% confidence interval 0.87–1.25; P  =   0.6555). Conclusions: Population‐based registry data in Japan show that the cancer stage at initial diagnosis is higher in women than in men, and women with localized or locally advanced bladder cancer have a worse prognosis compared with men.